Hungarian Monitoring, 4 October 1990 . [Magyar rádiófigyelő], 1990. október 4 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Transcripts of Hungarian national radio programs produced by the Hungarian Monitoring Unit of Radio Free Europe/Radio Liberty. A magyar országos rádióadók műsorainak a Szabad Európa Rádió/Szabadság Rádió Magyar Monitoring Osztálya által készített átiratai. International Politics: - First sitting of new German parliament - Presidential election campaign in Poland - Gasoline shortages in Czechoslovakia - Prisoners' strike in Estonia - Mitterrand in Saudi Arabia - Vatra Românească forms Association of Hungarianized Romanians - Romania Mare attacks Árpád Göncz Domestic Affairs: - Jeszenszky in New York - Miklós Németh on the opening up of the border one year ago - Agreements on the land reform plan - Election campaign Economy: - Ban on setting up studios - One-off help for those receiving low pensions - Recommendation on modifying law on family benefits - Conditions for influx of foreign capital Külpolitika: - Az össznémet parlament első ülése - Elnökválasztási kampány Lengyelországban - Benzinhiány Csehszlovákiában - Elítéltek sztrájkja Észtországban - Mitterrand Szaúd-Arábiában - A Vatra Românească létrehozta az Elmagyarosított Románok Szövetségét - A Romania Mare támadja Göncz Árpádot Belpolitika: - Jeszenszky New Yorkban - Németh Miklós az egy évvel korábbi határnyitásról - Egyeztetések a földprogramról - Választási kampány Gazdaság: - Stúdióalapítási tilalom - Kisnyugdíjasok egyszeri segélye - Javaslat a családi pótlékról szóló törvény módosítása - A külföldi tőke beáramlásának feltételei